'Ilm 'Alughati 'Al Nafsi Lildiraasaat Al Jami'iyyati - Ali, Asem Shehadeh Saleh (s.n, 2012)
This study deals with the issues in Arabic psycholinguistics. The study assumes that references in psycholinguistics need more explanation for the learners in Arabic and Islamic Universities. This study begins with definitions of psycholinguistics literally and terms